Implementasi Program Keluarga Harapan Sebagai Upaya Penanggulangan Kemiskinan di Kecamatan Jambangan Kota Surabaya - Febi Fauzan, Muhammad; Isbandono, Prasetyo (Universitas Negeri Surabaya, 2023)
The Family Hope Program is a conditional assistance program that aims to overcome poverty that occurs in Indonesia, the Family Hope Program has been issued by the government since 2007. However, the implementation of the Family Hope Program still has obstacles and has not been implemented optimally. This study uses a descriptive qualitative approach, in this study to examine the implementation of the Family Hope Program (PKH) in Jambangan District, Surabaya City using the theory proposed by George Edward III. The sampling technique uses observation, interviews, and documentation. The results of this study show that the implementation carried out in the sub-district has not been carried out optimally in the communication category, the problems found in the communication element have not been carried out optimally. Elements related to the implementation of the Family Hope Program (PKH), namely socialization that is carried out not in accordance with the Family Hope Program (PKH) implementation guidelines issued by the Ministry of Social Affairs (SOP), are still not precisely targeted at the beneficiaries, namely stakeholders concerned about receiving Family Hope Program assistance are still abusing authority by utilizing PKH assistance for personal interests. The researcher advised the Ministry of Social Affairs to re-coordinate with several other stakeholders, namely Districts, Sub-districts, Villages, RTs and RWs to conduct monitoring and evaluation. Keywords: Family Hope Program, Implementation, Poverty